Tactile perception of pleasantness in relation to perceived softness - Pasqualotto, Achille; Ng, Megan; Tan, Zheng Yee; Kitada, Ryo (Scientific reports, 2020)
The sense of touch allows us to infer objects’ physical properties, while the same input also produces affective sensations. These affective sensations are important for interpersonal relationships and personal well-being, which raises the possibility that tactile preferences are adapted to the characteristics of the skin. Previous studies examined how physical properties such as surface roughness and temperature influence affective sensations; however, little is known about the effect of compliance (physical correlate of softness) on pleasantness. Thus, we investigated the psychophysical link between softness and pleasantness . Pieces of human skin-like rubber with different compliances were pressed against participants’ fingers. Two groups of participants numerically estimated the perceived magnitude of either pleasantness or softness. The perceived magnitude of pleasantness and softness both increased monotonically as a function of increasing object compliance, levelling off at around the end of the stimulus range. However, inter-subject variability was greater for pleasantness than for perceived softness, whereas the slope of the linear function fit to the magnitude estimates was steeper for softness than for pleasantness. These results indicate that object compliance is a critical physical determinant for pleasantness, whereas the effect of compliance on pleasantness was more variable among individuals than the effect on softness was.